Guide to the Naturalized and Invasive Plants of Laikipia - Witt, Arne (CABI, 2017)
The impetus for the development of this Field Guide came about as a result of pleas from the community around the village of Doldol, Laikipia County, to initiate a control programme for Australian prickly pear [Opuntia stricta (Haw.) Haw.; Fabaceae], an invasive plant which was having a dramatic impact on livelihoods. However, a number of other exotic plants, which were less widespread, but had the potential of becoming invasive, were not seen as a potential problem. In order to avoid a similar situation from arising in the future, the community expressed a need for a Field Guide, which would include descriptions of naturalized and invasive species already present in, and those that were most likely to invade Laikipia County and, information on how best to manage them. An additional impetus was to contribute to the four main objectives of the National Strategy and Action Plan for the Management of Invasive Species in Kenya's Protected Areas. The Field Guide contributes in some or other way to all of these objectives which are to (i) Enhance awareness of invasive species to relevant actors; (ii) Prevent new invasions, manage established invasions and rehabilitate degraded habitats; (iii) Enhance research, monitoring and information management on invasive species; and (iv) Enhance capacity, resource mobilization and coordination. Extensive surveys revealed the presence of a number of introduced plant species which had escaped cultivation and established populations in the 'wild' to the detriment of natural resources and the people that depend on them. Introduced succulents, especially those in the genus Opuntia (Cactaceae), were found to be the most widespread and abundant invasive species in the semi-arid regions in the north and east of Laikipia County. Other succulents, those in the genus Bryophyllum (Crassulaceae), were also found to have escaped cultivation and were locally abundant. In the higher rainfall areas to the west and southwest, introduced trees such as black wattle (Acacia mearnsii De Wild.; Fabaceae) and Australian blackwood (Acacia melanoxylon R. Br.; Fabaceae) and the shrubs/climbers, Mauritius thorn [Caesalpinia decapetala (Roth) Alston; Fabaceae] and yellow cestrum (Cestrum aurantiacum Lindl.; Solanaceae), were invasive. Introduced plants, which have the potential to become problematic in Laikipia, unless eradicated or controlled, have also been included in the Guide. This includes species such as famine weed (Parthenium hysterophorus L.; Asteraceae) and 'mathenge' [Prosopis juliflora (Sw.) DC.; Fabaceae], which are already abundant in areas adjoining the County.